Analyzing Supply and Demand Response of Indonesian Cloves in International Market - Vina Panca Margaretha Siringoringo; Djaimi Bakce; Novia Dewi (Indonesian Journal of Multidisciplinary Science, 2023)
Indonesia is the world's largest clove producer and consumer. In addition, Indonesia is also a world exporter and importer of cloves, with the largest harvest area in the world. This study aims to analyze the supply and demand responses of Indonesian cloves in the international market. The study used time series data for the period 1985–2019. The research used an econometric design by building a simultaneous equation model. Data analysis using the two-stage Least Square method. The results showed that the factors that are responsive in the short term are the exchange rate of the rupiah against the US dollar, demand for Indonesian cloves, Comoros and Tanzania clove production, world clove prices t-1, and United Arab Emirates GDP per capita, while in the long term are Indonesian and Madagascar clove harvest area,  the rupiah exchange rate against the US dollar, Indonesian clove demand, Comoros, Madagascar and Tanzania clove production, world clove prices t-1, and United Arab Emirates GDP per capita.